Transformasi Konsep Martabat Perempun Tanimbar Dalam Hubungan Dengan Adat Harta Pakai Dan Harta Buang - Londar, Koleta Lempitenan (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2024)
The Tanimbar society views women as a source of life for all mankind. In married life, women’s dignity is highly respected with customary rules or laws called harta pakai and harta buang. However, in the development of customary rules, the laws began to fade in the face of various other types of laws such as civil law and religious law. The main question of this study is: “How is the transformation of the Tanimbar people’s views on the dignity of women in the relationship between the practice of harta pakai and harta buang in the context of the complexity of law and values?” The purpose of this study is to describe the complexity of law and values ​​that affects the transformation of the concept of women in Tanimbar. This study used is a qualitative method and the data presented is qualitative or descriptive. Data are collected through interview and observation techniques. The findings indicate that the exchange of property in marriage practices illustrates a sign of appreciation and gratitude for women who have cared for and raised their daughters until they enter the stage of marriage. However, in practice, this appreciation begins to change and makes women like mere objects or commodities.